Answer:
Um theres no question or picture. Or document.
Step-by-step explanation:
![k:\ y=m_1x+b_1\\\\l:\ y=m_2x+b_2\\\\k\ ||\ l\iff m_1=m_2\\\\k\ \perp\ l\iff m_1m_2=-1](https://tex.z-dn.net/?f=k%3A%5C%20y%3Dm_1x%2Bb_1%5C%5C%5C%5Cl%3A%5C%20y%3Dm_2x%2Bb_2%5C%5C%5C%5Ck%5C%20%7C%7C%5C%20l%5Ciff%20m_1%3Dm_2%5C%5C%5C%5Ck%5C%20%5Cperp%5C%20l%5Ciff%20m_1m_2%3D-1)
We have:
![k:\ 9x+7y=6\ \ \ |-9x\\\\7y=-9x+6\ \ \ \ |:7\\\\y=-\dfrac{9}{7}x+\dfrac{6}{9}\to m_1=-\dfrac{9}{7}\\\\l:\ y=m_2x+b\\\\l\ \perp\ k\iff-\dfrac{9}{7}m_2=-1\ \ \ \ |\cdot\left(-\dfrac{7}{9}\right)\\\\m_2=\dfrac{7}{9}\to\ l:\ y=\dfrac{7}{9}x+b](https://tex.z-dn.net/?f=k%3A%5C%209x%2B7y%3D6%5C%20%5C%20%5C%20%7C-9x%5C%5C%5C%5C7y%3D-9x%2B6%5C%20%5C%20%5C%20%5C%20%7C%3A7%5C%5C%5C%5Cy%3D-%5Cdfrac%7B9%7D%7B7%7Dx%2B%5Cdfrac%7B6%7D%7B9%7D%5Cto%20m_1%3D-%5Cdfrac%7B9%7D%7B7%7D%5C%5C%5C%5Cl%3A%5C%20y%3Dm_2x%2Bb%5C%5C%5C%5Cl%5C%20%5Cperp%5C%20k%5Ciff-%5Cdfrac%7B9%7D%7B7%7Dm_2%3D-1%5C%20%5C%20%5C%20%5C%20%7C%5Ccdot%5Cleft%28-%5Cdfrac%7B7%7D%7B9%7D%5Cright%29%5C%5C%5C%5Cm_2%3D%5Cdfrac%7B7%7D%7B9%7D%5Cto%5C%20l%3A%5C%20y%3D%5Cdfrac%7B7%7D%7B9%7Dx%2Bb)
We know. The line <em>l</em> passes throught the point (9, -7). Substitute the coordinates of the poin to the equation of line<em> l </em>:
![-7=\dfrac{7}{9}\cdot9+b\\\\-7=7+b\ \ \ \ |-7\\\\b=-14](https://tex.z-dn.net/?f=-7%3D%5Cdfrac%7B7%7D%7B9%7D%5Ccdot9%2Bb%5C%5C%5C%5C-7%3D7%2Bb%5C%20%5C%20%5C%20%5C%20%7C-7%5C%5C%5C%5Cb%3D-14)
![y=\dfrac{7}{9}x-14\ \ \ \ |\cdot9\\\\9y=7x-126\ \ \ \ |-9y\ |+126\\\\7x-9y=126](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B7%7D%7B9%7Dx-14%5C%20%5C%20%5C%20%5C%20%7C%5Ccdot9%5C%5C%5C%5C9y%3D7x-126%5C%20%5C%20%5C%20%5C%20%7C-9y%5C%20%7C%2B126%5C%5C%5C%5C7x-9y%3D126)
Answer: ![y=\dfrac{7}{9}x-14\to7x-9y=126](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B7%7D%7B9%7Dx-14%5Cto7x-9y%3D126)
5 is the answer, you are welcome.
Answer: D
Step-by-step explanation:
To find the difference, we want to make sure both denominators are equal.
![\frac{(6x)(2x-3)}{(6x)(3x^2)} -\frac{(3x^2)(x+2)}{(3x^2)(6x)}](https://tex.z-dn.net/?f=%5Cfrac%7B%286x%29%282x-3%29%7D%7B%286x%29%283x%5E2%29%7D%20-%5Cfrac%7B%283x%5E2%29%28x%2B2%29%7D%7B%283x%5E2%29%286x%29%7D)
Now that the denominators are equal, we can distribute and multiply out.
![\frac{12x^2-18x}{18x^3} -\frac{3x^3+6x^2}{18x^3}](https://tex.z-dn.net/?f=%5Cfrac%7B12x%5E2-18x%7D%7B18x%5E3%7D%20-%5Cfrac%7B3x%5E3%2B6x%5E2%7D%7B18x%5E3%7D)
With the fractions multiplied out, we can actually put it into one large fraction.
![\frac{12x^2-18x-3x^3-6x^2}{18x^3}](https://tex.z-dn.net/?f=%5Cfrac%7B12x%5E2-18x-3x%5E3-6x%5E2%7D%7B18x%5E3%7D)
Let's subtract the top expression.
![\frac{-3x^3+6x^2-18x}{18x^3}](https://tex.z-dn.net/?f=%5Cfrac%7B-3x%5E3%2B6x%5E2-18x%7D%7B18x%5E3%7D)
This may seem like our final answer, but we can actually factor out an 3x in the numerator and denominator.
![\frac{(3x)(-x^2+2x-6)}{(3x)(6x^2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%283x%29%28-x%5E2%2B2x-6%29%7D%7B%283x%29%286x%5E2%29%7D)
With the 3x factored out, they cancel out because 3x/3x=1.
Our final answer is:
![\frac{-x^2+2x-6}{6x^2}](https://tex.z-dn.net/?f=%5Cfrac%7B-x%5E2%2B2x-6%7D%7B6x%5E2%7D)
The answer is going too be -4 or you can write it as (0,-4) I think